CDM Potential for Rural Transition in China Case Study: Options in Yinzhou District, Zhejiang Province - Xingshu Zhao; Axel Michaelowa (Hamburg Institute of International Economics (HWWA), 2004)
This paper aims to examine the potential of the Clean Development Mechanism (CDM) to address energy- related issues during the rural transition process in China, using a case study of quickly urbanizing and industrializing Yinzhou district in coastal Zhejiang province. Yinzhou's per capita GDP reached US 3100 in 2002, three times China's average, and is targeted to achieve 10,000 in 2020. We assess the current energy status of Yinzhou, and provide projections of energy consumption and CO2 emissions up to the year 2020. Energy resource shortages and limited possibilities to obtain coal-fired electricity from national grid illustrate the opening gap between energy supply and demand. We find that Yinzhou's CDM potential is concentrated in efficiency improvement on the demand side. In that context, we suggest to systematically explore the CDM potential in the industrial sector. Projects will have to involve many stakeholders and the necessary local capacity has to be built. These CDM projects can be considered as killing three birds with one stone, namely maintaining continuous economic growth, alleviating local environmental pollution as well as mitigating global climate change.
Keywords: Q58; Q54; 330; Clean Development Mechanism; China; urbanization; energy efficiency; Urbanisierung; Industrialisierung; Klimaschutz; Clean Development Mechanism; Energiesparen; Tschekiang